Isolation, screening and characterization of xylose-fermenting yeasts isolated from sawdust - Adelabu Blessing; Michael Taiwo; Soetan OO (Annals of Tropical Research)
Yeasts have been less frequently reported as xylanase producers compared to bacteria and filamentous fungi. Different cellulosic materials including sawdust are produced on a large scale and these can be used for the production of useful enzymes such as xylanases. Xylanases are a group of enzymes that hydrolyze plant fibers made of xylan hemicellulose. Xylose-fermenting yeasts isolated from soil at a wood processing factory were isolated and qualitatively and quantitatively screened for xylanase production using xylose supplemented medium and congo red as indicator. Xylanase enzyme was produced using different xylose concentrations (0.5%, 1.0%, 1.5% and 2.0%). Pichia chambardii isolate, which was later identified as Wickerhamomyces chambardii by molecular techniques, showed the highest xylanase activity of 199.31U mL-1. Maximum xylanase activity (275.83U mL-1) was achieved at 1.5 %w/v xylose. This study showed that yeasts have a high potential for the production of xylanase enzymes.